Effect of Refractory on Nonmetallic Inclusions in Si–Mn‐Killed Steel. Issue 12 (17th September 2019) - Deng, Zhiyin; Cheng, Liu; Chen, Lei; Zhu, Miaoyong
Abstract : Some laboratory experiments are carried out to study the effect of different refractories on the original and exogenous inclusions in Si–Mn‐killed steel. As expected, it is found that Al2 O3 refractory causes high melting points of both SiO2 –Al2 O3 ‐MnO system and SiO2 –Al2 O3 ‐CaO system inclusions, while MgO crucible reduces the melting points of both systems of inclusions to a certain extent. The purity of MgO refractory is crucial for tire cord steel grades, and even 0.3% of Al2 O3 impurity in refractory results in an evident increase (by 10%‐20%) of Al2 O3 content in the inclusions. Similar to Al‐killed steel grades, MgO·Al2 O3 spinel can also be stable in Si–Mn‐killed steel due to the effect of MgO refractory, and MgO and Al2 O3 inclusions can transform into MgO·Al2 O3 spinel. These inclusions should be strictly controlled during refining process. High‐purity and high‐quality MgO refractory as well as high‐quality alloys are recommended for Si–Mn‐killed steel grades, and Al2 O3 ‐based refractory should be avoided. Abstract : Laboratory experiments are carried out to study the effect of refractory on the inclusions in Si–Mn‐killed steel. The influence of the impurity in MgO refractory on the composition and the melting point of the original inclusions in steel are investigated, and the effect of MgO refractory on the exogenous inclusions (MgO, MgO·Al2 O3 and Al2 O3 ) are also simulated and discussed.